Mencegah Konflik Rumah Tangga di Era Digital: Kontekstualisasi Hadis Al-ḥamwu Al-mawt dalam Shahih Bukhari Nomor 5232 - Aprilia, Mery; Azwar, Alfi Julizun; Almunadi, Almunadi (Jurnal Riset Agama, 2025)
This research examines contextualization of hadith al-ḥamwu al-mawt in an effort to prevent household conflicts in the digital era. The method used is qualitative research based on library research (literature), with primary data sources taken from the book of Sahih Bukhari. The results showed that the hadith of al-ḥamwu al-mawt listed in Shahih Bukhari number 5232 is often used to prevent household conflicts in the digital era. Shahih Bukhari number 5232 is often quoted in the context of domestic relations, especially relationships with in-laws, father and mother-in-law, and other close relatives of the couple. The phrase al- al-ḥamwu al-mawt in this hadith is a strong warning against potential dangers that can arise from uncontrolled interactions with in-laws and other family members, such as a rift between the in-laws. The study also found that the transformation of forms of interaction in the digital era has also increases the risk of household conflicts, especially through infidelity, which is now easier to easier to occur because it is supported by technological advances.